Implementation and Analysis of Chemical Hazard Risk Assessment (CHRA) at a Petrochemicals Company, Malaysia - Suziyana, Mat Dahan; Mohd Yusof, Taib; Nurhaizan, Mohd Zainudin; Fadzida, Ismail; Ahmad Nazif, Noor Kamar (Universiti Malaysia Pahang, 2012)
Safety and health management system has started since last thirty years ago. At that time, the systems focused on protecting and informing workers with the assumption that workplace accidents were generally the result of individual unsafe acts. Safety standards were poor if compared with today, until the introduction of legislation in the 1970s. It was the first time, law placed responsibilities on employers and managements for ensuring the health and safety of the workers and the general public. Organizations management were started to view health and safety as an integral part of their business management and kept improving it by involving governmental and non-governmental organizations. Many organizations believed in effective health and safety management as one of the major factors for their profitability, not only contributing to reduce the cost of damage, down time and compensation, but also has significant effects on maximizing team and individual performance. An assessment known as Chemical Hazard Risk Assessment (CHRA) was carried out continuously for the purpose of safety and health improvement at workplace. In this paper, CHRA that was conducted in one of petrochemical companies in Malaysia is reported. Two work units have been chosen in which the workers were exposed to different types of chemical, duration of exposure and different mode of handling. The purpose of this assessment is to ensure that the workers are in safe workplace environment. In this assessment, hazards of every chemical were studied by referring to Material Safety Data Sheet or Chemical Safety Data Sheet which provided by chemical suppliers. Every task performed by workers was investigated to find out the safety work practice and degree of hazards released by the chemicals. Once the assessment was completed, actions required to control the risk at the workplace were determined. Results revealed that some work units were good at meeting the safety standards, but with CHRA, better safe workplace could be provided. More intensive enforcement by government agencies such as Department of Organization Safety and Health (DOSH) are required to ensure employers pursue relevant initiatives to meet the safety laws and regulations.